Numerical Simulation and Experimental Verification of the Two-phase Flow Characteristic of the Automotive Gear - Zou Lin Du Mingya Jia Bing Xu Jinli (Jixie chuandong, 2019)
Aiming at the two-phase flow characteristics of the automotive gear, based on the PLIC-VOF algorithm, the three-dimensional churning process model of the gear is numerically calculated by Matlab software. The influence of different rotational speed and immersion depth as well as viscosity on churning power loss of the gear is discussed. Then the three-dimensional churning model of the gear is simulated by Fluent. The power loss experimental and the visual experiment are conducted. The results show that the PLIC-VOF algorithm is suitable for calculating churning loss of the gear. The turbulence of oil distribution increased with the rotational speed. The churning power loss increased with rotational speed and immersion depth as well as viscosity, among which the rotational speed has the greatest influence.